DAS-VSP interferometric imaging: CO2CRC Otway Project feasibility study - Sidenko, Evgeny; Tertyshnikov, Konstantin; Bona, Andrej; Pevzner, Roman (SOC EXPLORATION GEOPHYSICISTS, 2021)
Recent advancements in distributed acoustic sensing (DAS) technology open new ways for borehole-based seismic monitoring of CO2 geosequestration. Compared to 4D surface seismic monitoring, repeated vertical seismic profiling (VSP) surveys with DAS receivers considerably reduce the cost and invasiveness of time-lapse CO2 monitoring. However, standard borehole imaging techniques cannot provide the same level of reservoir illumination as 3D surface seismic. The performance of VSP imaging can be significantly improved with interferometric utilization of free-surface multiples. We have developed a feasibility study of interferometric imaging with a synthetic walkaway VSP data set, followed by its application to field walkaway VSP data recorded by conventional borehole geophones and two types of DAS (standard and engineered fibers). Both experiments (synthetic and field) demonstrate that interferometric imaging is a viable method to extend the subsurface image beyond the coverage of standard VSP imaging. Specifically, the interferometry approach provides a more detailed upper section of the subsurface, whereas standard migration of primary reflections provides a more detailed bottom part of the image. Comparison of the standard and engineered fibers indicates that both fibers are sensitive to free-surface multiples, but the engineered fiber provides a much higher signal-to-noise ratio; thus, it is preferable for interferometric imaging with multiples. The result obtained with the engineered DAS cable indicates that in the depth range suitable for both methods, the VSP interferometric image of the reflectors is comparable to the surface seismic image. The experiment on the field DAS data proves that DAS is sensitive enough to record the nonprimary wavefield for imaging and monitoring of the subsurface.